(untitled) (Fiep Bulletin - online, 2014)
The use of anabolic steroids in athletes and young people has increased over the years, however, there are still few empirical and epidemiological data related to the theme and this population. For this reason, research has been taken, with the aim of presenting the socio demographic and desire for body modification in users of anabolic steroids. Therefore, the participants answered a questionnaire specifically designed for the research and the answers were presented according to their prevalence. It was found a prevalence of 5.0% of consumption of steroids and / or use of anabolic steroids, primarily in males, with a mean age of approximately 23 years (SD = 8.8). It was also observed that most users practice diets, dietary supplements and consume medicines for alteration of body weight. Regarding the desire for body modification, it was found that most want to change something in the body and is not satisfied with it. The results were discussed with relevant literature, specifically related to cultural aspects and their influence to the ideal body image.